Pemetaan Industri Kreatif Sektor Kerajinan Blangkon Terhadap Dampak Ekonomi Masyarakat Dengan Pengukuran Produktivitas - Azizah, Hidayati, Muchlison Anis S.T.,M.T, Etika Muslimah, S.T., M.M., M.T (2015)
Craft industry is one sector which contributes greatly to the economy of the community. The creative industry has 14 sectors according to ISIC statutes (Classification of Indonesia's Business Sector Books). This research was conducted in the District Serengan Surakarta by mapping the creative industries in the District Serengan Surakarta against the economic effects of people affected by the four indicators, namely labor, capital, the amount of production and revenues. Serengan subdistricts dominated by one sector, namely the craft sector by 34%. However, based on the number and percentage of results that has the largest number of craft blangkon ie by 26% which is located in the Village Serengan. To determine and influence the development of creative industries to the economy, the productivity measured by the ratio between the effectiveness (output) with efficiency (input). Results of the assessment of each indicator by comparing 2014 and 2015. There is an increase from the previous year, meaning that the greater the productivity value, the better the achievement of the targets. Productivity measurement results obtained are based on indicators of employment in 2014 obtained value productivity of 390 units / person in 2015 amounted to 667 units / person, the capital in 2014 and 2015 gained Rp1.3 Rp 2.7. The results above show an increase from 2014 to 2015. The total productivity index value in 2014 amounted to 224% increase in 2015 amounted to 327%. This means that the effectiveness of the achievement of the quality level of the efficiency of resource use have increased. Keywords: creative industry, mapping, Productivity.